Thalictrum hengduanshanense and T. longistipitatum (Ranunculaceae), two new species from southeastern Xizang and northwestern Yunnan, China - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Thalictrum hengduanshanense and T. longistipitatum (Ranunculaceae), two new species from the southern Hengduan Mountains region in southeastern Xizang and northwestern Yunnan, China, are illustrated and described. Morphologically T. hengduanshanense is most closely similar to T. tsawarungense in having narrowly oblanceolate-linear filaments of stamens and apically slightly recurved styles, but differs by having laxly branched, corymb-like (vs. narrowly paniculiform) inflorescences and larger (ca. 9 mm vs. 4.5‒7 mm long), narrowly lunate (vs. broadly lunate) achenes (body width/body length = ca. 1/3 vs. ca. 1/2). Thalictrum longistipitatum is closely similar to T. hengduanshanense in habit and in having narrowly oblanceolate-linear filaments of stamens, apically slightly recurved styles, and long stipitate achenes, but differs by having apically abruptly recurved (vs. straight) pedicels and shorter styles (ca. 1 mm vs. ca. 2 mm long). Chromosome numbers of T. longistipitatum (2n = 14), T. rostellatum (2n = 28), T. tsawarungense (2n = 14) and T. wangii (2n = 14) are reported here for the first time.